1991
DOI: 10.1021/es00019a009
|View full text |Cite
|
Sign up to set email alerts
|

High-temperature removal of cadmium compounds using solid sorbents

Abstract: Emission of cadmium compounds is a major problem in many combustors and incinerators. In the present work, the use of solid sorbents for removal of cadmium compounds from high-temperature flue gases is investigated. The sorbents tested were silica, alumina, kaolinite, emathlite, and lime. Compounds containing aluminum oxide show high cadmium removal efficiency. In particular, bauxite has the highest rate and capacity for cadmium capture. The overall sorption process is not just physical adsorption, but rather … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
77
1
2

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(86 citation statements)
references
References 0 publications
4
77
1
2
Order By: Relevance
“…64,66,77,153 Sorbents may encounter mass-transfer limitations due to outer-surface reactions producing a metal sorbent complex that blocks the inner pore volume. 139 This has been observed for lead-kaolinite reactions by Scotto et al 66,147 They also reported limitations of sorbent capture of lead in chlorine environments. Gullet and Rangunathan 25 also concluded that the effectiveness of the sorbent applications for metals control should not only be demonstrated by chemical reactivity but also by the suppression of the formation of finer particles.…”
Section: Sorbent Methodologiesmentioning
confidence: 69%
See 1 more Smart Citation
“…64,66,77,153 Sorbents may encounter mass-transfer limitations due to outer-surface reactions producing a metal sorbent complex that blocks the inner pore volume. 139 This has been observed for lead-kaolinite reactions by Scotto et al 66,147 They also reported limitations of sorbent capture of lead in chlorine environments. Gullet and Rangunathan 25 also concluded that the effectiveness of the sorbent applications for metals control should not only be demonstrated by chemical reactivity but also by the suppression of the formation of finer particles.…”
Section: Sorbent Methodologiesmentioning
confidence: 69%
“…25,64,66,[138][139][140][141][142][143][144][145][146][147][148][149] Shadman and et al 139,[150][151][152] have demonstrated the effectiveness of sorbents (alumina, bauxite, emathlite, kaolinite, silica, limestone) for the capture of lead, cadmium, and other alkali metal vapors. Wu et al 181 extended their earlier studies to the development of a multifunctional sorbent for capture of sulfur dioxide, alkali metals, and lead.…”
Section: Sorbent Methodologiesmentioning
confidence: 99%
“…This could be a problem for GBF operation but is unlikely to occur as these extreme conversions are not realistically obtained. Kaolin, bauxite, and emathlite were all found to be capable of removing alkali from coal conversion streams (Uberoi et al, 1990). Kaolin and emathlite adsorption of alkali was an irreversible process.…”
Section: Clay For the Control Of Alkalimentioning
confidence: 94%
“…[4][5][6][7][8][9] CdO or PbO reacts with various sorbents at temperatures Ͼ700°C; MO ⅐ Al 2 O 3 , MO ⅐ 2 SiO 2 , and MO ⅐ Al 2 O 3 ⅐ 2 SiO 2 (where M denotes Pb or Cd) have been detected as reaction products by X-ray diffraction techniques. 8,9 These compounds are less soluble in acidic solutions. 8,9 Clay is a useful resource that can serve as an important raw material in the firebrick/brick industries.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 These compounds are less soluble in acidic solutions. 8,9 Clay is a useful resource that can serve as an important raw material in the firebrick/brick industries. Clay has been found to be effective in immobilizing heavy metals; it therefore would be of great practical application to (1) use clay to sorb Cr(VI) from the wastewater of plating and leather tanning industries, and then detoxify the Cr(VI)-sorbed clay; and (2) mix clay with Cr(VI)-containing industrial sludge, and then immobilize the Cr.…”
Section: Introductionmentioning
confidence: 99%